Crossing sea state and rogue wave probability during the Prestige accident. Issue 10 (31st October 2015) - Trulsen, Karsten; Nieto Borge, José Carlos; Gramstad, Odin; Aouf, Lotfi; Lefèvre, Jean–Michel
Abstract: We discuss the crossing sea state and the probability of rogue waves during the accident of the tanker Prestige on 13 November 2002. We present newly computed hindcast spectra for every hour during that day at nearby locations, showing the development of a bimodal sea state with two wave systems crossing at nearly right angle. We employ four different nonlinear models capable of computing the phase‐resolved sea surface from the hindcast spectra, allowing us to estimate statistics for the occurrence of rogue waves. At the location and moment of the accident, the models give expected values for the kurtosis κ = 3.0119 ± 0.0078. The models coincide that the maximum crest elevation was about 5–6% larger than the expected maximum crest elevation in a Gaussian sea at the moment of the accident. We also conclude that the possible nonlinear interaction between the two crossing wave systems practically did not modify neither the kurtosis nor the largest crest elevation. Key Points: Discuss the crossing sea state and rogue wave probability during the Prestige accident